Burnout Syndrome and Nurses’ Performance at Cibabat Regional Public Hospital - Fatma Nur Fauziya; Maria Widiawati; Ika Suhartati (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
Burnout syndrome is characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment, commonly experienced by nurses who work under high workload pressures. This study aimed to analyze the relationship between burnout syndrome and nurses’ performance in adult inpatient wards at Cibabat Regional Public Hospital in 2025. A quantitative correlational design with a cross-sectional approach was applied, involving 49 nurses selected through total sampling. Burnout levels were assessed using the Maslach Burnout Inventory (MBI), while performance was measured using a standardized nursing performance questionnaire. Data were analyzed using the Chi-Square test. The results showed that the majority of nurses had low levels of burnout (55.1%) and demonstrated good performance (57.1%). A statistically significant association was found between burnout syndrome and nurses’ performance (p = 0.002), indicating that nurses with higher burnout levels tended to show lower performance. These findings emphasize the importance of organizational support, balanced workloads, and regular monitoring to reduce burnout risk and enhance nursing performance.